Carbon Palma Ratio: A new indicator for measuring the distribution inequality of carbon emissions among individuals. (20th December 2019) - Pan, Xunzhang; Wang, Hailin; Wang, Ziwei; Lin, Lu; Zhang, Qi; Zheng, Xinzhu; Chen, Wenying
Abstract: Combating global climate change calls for all countries to accelerate emissions reductions, and equity is an important guiding principle. A new indicator – the carbon Palma ratio, extended from the income Palma ratio and defined as the ratio of the total emissions of the top 10% emitters to those of the bottom 40% – is proposed, which provides a new perspective to inform the international community and the public of the distribution inequality of carbon emissions among individuals. The ratio is quantified within and across countries, by applying an elastic relationship between individual emissions and income. Results show that the carbon Palma ratios within most developing countries are overall high, suggesting them to focus more on coordinating regional and income differences and mainly guide high emitters to mitigate, so as to improve emissions and income equity simultaneously. The carbon Palma ratios within developed countries are comparatively smaller; however, the greater historical responsibilities to warming suggest them to substantially reduce emissions of all citizens, so as to enhance national mitigation contributions systematically. At a global scope, the current carbon Palma ratio is observably higher than within any country, reflecting an extremely severe inequality when looking at individual emissions beyond territorial limitations. The regional decomposition of emitters further suggests developed countries to take the lead in the post-Paris era in ratcheting up mitigation and climate finance ambition. Graphical abstract: Image 1 Highlights: Carbon Palma ratio is proposed to measure individual emissions inequality. The ratio provides a new perspective to quantify and inform inequality. The ratios in developed countries are overall lower than in developing countries. The global ratio reflects an extremely severe inequality across the world. Decomposition suggests developed countries to enhance mitigation and finance.